Mimicking biofilm formation and development: Recent progress in in vitro and in vivo biofilm models - Guzmán-Soto, Irene; McTiernan, Christopher; Gonzalez-Gomez, Mayte; Ross, Alex; Gupta, Keshav; Suuronen, Erik J.; Mah, Thien-Fah; Griffith, May; Alarcon, Emilio I. (iScience, 2021)
Biofilm formation in living organisms is associated to tissue and implant infections, and it has also been linked to the contribution of antibiotic resistance. Thus, understanding biofilm development and being able to mimic such processes is vital for the successful development of antibiofilm treatments and therapies. Several decades of research have contributed to building the foundation for developing in vitro and in vivo biofilm models. However, no such thing as an “all fit” in vitro or in vivo biofilm models is currently available. In this review, in addition to presenting an updated overview of biofilm formation, we critically revise recent approaches for the improvement of in vitro and in vivo biofilm models. [Display omitted] Microbiology; Microbiofilms